Atypical femoral fracture associated with delayed union for which the cessation of alendronate and daily administration of teriparatide contributed to fracture healing: histopathological evidence of the enhancement in bone formation parameters. (2nd January 2020) - Kondo, Naoki; Miyasaka, Dai; Watanabe, Yo; Sato, Hiroe; Kanda, Toshihiro; Endo, Naoto
Abstract: A female patient with systemic lupus erythematosus developed an atypical femoral fracture of the left femur after 5 years of glucocorticoid and alendronate therapy. We performed intramedullary nailing. However, 1 week later, we performed a revision surgery using a locking plate and an iliac bone graft because of displacement at the fracture site. At this stage, alendronate was discontinued and daily teriparatide was introduced and continued for 24 months. Twenty months after the revision surgery, a re-revision surgery was performed with an iliac bone graft because of breakage of the locking plate and fracture non-union. Fracture healing was eventually obtained 15 months after the re-revision surgery. Biopsies of the ilium before the treatment and 20 months after daily teriparatide treatment were evaluated. The histology revealed that proliferating osteoid and cuboidal osteoblasts were detected around the osteoid tissue after teriparatide treatment. Bone histomorphometry findings showed that bone volume parameters and osteoid parameters prominently increased with the teriparatide treatment, but not bone resorption parameters. Laboratory findings revealed the elevation of bone-specific alkaline phosphatase (24 U/L at 7 months) compared to its pre-teriparatide level (8.1 U/L) and increased bone mineral density of the hip (from −0.2 to 0.0 in T -score). These data indicated that the discontinuation of alendronate and initiation of teriparatide treatment activated bone-forming ability in our patient and may have contributed to fracture healing.